Evidence-oriented approaches in development cooperation: experiences, potential and key issues - Paul Marschall (Deutsches Institut für Entwicklungspolitik (DIE), 2018)
The use of more evidence as an instrument for achieving higher impact in development cooperation (DC) is a major topic in current discussions. This discussion paper is a contribution to answering three questions. First, how is evidence currently provided in DC? Second, what are ways of using evidence in this regard? Third, what is the potential of considering evidence in policy-making in the near future? This refers to how and in what context it is usable. Evidence is a term with several meanings and connotations. Based on a broad definition of evidence, a comprehensive conceptual approach is developed for understanding the scope, value and relevance of evidence in policy-making. Until recently, evidence about what works in DC was mostly only available for specific settings. Within the Millennium Development Goals, those shortcomings became obvious and things started to change. Monitoring, results-based management and results-based approaches were installed and provide evidence for different purposes. The number of evaluations and their quality increased. International networks and organisations now provide capacity-building for delivering more and better evidence. There are institutes and persons who aim at awareness-raising in this regard at the level of decision-making and administrative bodies. Evidence matters in DC policy-making. It is used both symbolically, for increasing the credibility of the decision-makers and their decisions, and instrumentally, to adjust knowledge and to improve decision-making. Because of a strong push from national and international initiatives, the awareness of the value of evidence for DC has risen in a striking way, but the adoption of evidence in different settings is still rather mixed, namely as a consequence of complexities in real-world settings and other existing barriers. There are still enormous problems in translating evidence into practical use due to less appropriate transmission formats. Currently, social media and marketing campaigns, as used by the Copenhagen Consensus (CC) Centre, are important instruments for attracting attention. Ranking schemes – including the value-for-money of different interventions, as provided by the CC – are welcomed, because they are transparent and easy to get. However, such menus are often only used for “cherry picking”. In policy-making, available evidence is mostly only one of several inputs. Pathways to success are based on accompanying measures, including ongoing policy advice and an understanding about the joint production of required evidence. This approach can help to identify missing evidence, provide the available pieces of evidence in an appropriate quality and strength, and contribute to the consideration of evidence in policy-making in a reasonable way.
Keywords: 330; Deutsche + Europäische + multilaterale Entwicklungspolitik; Wirksamkeit und Evaluierung